An Identity Reflection through the Language Style Used by the Main Character in The Bear TV Series - Ghaniyah, Amira Qonita Syifaul; Sugiharti, Dona Rahayu (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This study aims to identify the types of language styles employed by the main character in The Bear TV series and to analyze how the most dominant styles reflect the main character‘s identity. According to Joos (1967), language style is defined as an individual‘s manner of communication, which is adjusted according to specific contexts and situations. This study adopts a qualitative approach utilizing a content analysis design to collect, categorize, and interpret relevant data from the main character‘s utterances throughout the TV series. The theoretical framework guiding this study is Joos‘ (1967) Five Clocks theory, which categorized language styles into five types: frozen, formal, consultative, casual, and intimate. Based on the analysis of the main character‘s utterances, three of the five language styles were identified: consultative (5 instances), casual (51 instances), and intimate (16 instances). Among these, the casual style emerged as the most frequently used. The predominance of the casual style indicates that the main character exhibits an egalitarian identity and tends to minimize hierarchical distinctions. This result is particularly significant given the hierarchical nature of professional kitchen environments, where strict chains of command are typically upheld. Despite holding the position of head chef, the main character demonstrates a preference for fostering collaborative and equal relationships with co-workers, as evidenced by his consistent use of casual style. This study highlights how language style functions as a reflection of the main character‘s identity, offering insight into the main character‘s personality, particularly his intense emotions and perfectionism, as conveyed through recurring linguistic choices across various situational and conversational contexts.